Answer:
![5x= 15](https://tex.z-dn.net/?f=5x%3D%2015)
Step-by-step explanation:
Given
![3x - 5 = -2x +10](https://tex.z-dn.net/?f=3x%20-%205%20%3D%20-2x%20%20%2B10)
Required
Write the variables and constants on different sides
![3x - 5 = -2x +10](https://tex.z-dn.net/?f=3x%20-%205%20%3D%20-2x%20%20%2B10)
Add 2x to both sides
![2x + 3x - 5 =2x -2x +10](https://tex.z-dn.net/?f=2x%20%2B%203x%20-%205%20%3D2x%20-2x%20%20%2B10)
![5x - 5 =10](https://tex.z-dn.net/?f=5x%20-%205%20%3D10)
Add 5 to both sides
![5x - 5 + 5 = 10 + 5](https://tex.z-dn.net/?f=5x%20-%205%20%2B%205%20%3D%2010%20%2B%205)
![5x= 10 + 5](https://tex.z-dn.net/?f=5x%3D%2010%20%2B%205)
![5x= 15](https://tex.z-dn.net/?f=5x%3D%2015)
Hence, the equation is
![5x= 15](https://tex.z-dn.net/?f=5x%3D%2015)
Solving further [divide both sides by 5]
![x = 3](https://tex.z-dn.net/?f=x%20%3D%203)
Answer:
tüm Türkiye'ye gönderilir ve hangi
Step-by-step explanation:
Metin kutusuna yapıştırmak için klibe dokunun.
Only option 1 and 4 are true.
Points S, U, and T are the midpoints of the sides of ΔPQR.
ΔSUT is inside of ΔPQR. Points S, U, and T are the midpoints of ΔPQR.
Which statements are correct? Check all that apply.
1. QP = UT
2. One-halfTS = RQ
3. SU = PR
4. SU ∥ RP
5. UT ⊥ RP
Given to us,
S, U, and T are the midpoints of the sides of ΔPQR.
Using Triangle Midpoint Theorem, which states that the line segment connecting the midpoints of two sides of a triangle is parallel to the third side and is congruent to one half of the third side.
Therefore, only option 1 and 4 are true.
To know more visit:
brainly.com/question/8943202
The polynomial 9x^5+36x^4+189x^3 in factored form is ![-9 x \times x \times x \times(x-7) \times(x+3)](https://tex.z-dn.net/?f=-9%20x%20%5Ctimes%20x%20%5Ctimes%20x%20%5Ctimes%28x-7%29%20%5Ctimes%28x%2B3%29)
<u>Solution:</u>
Given, polynomial equation is ![-9 x^{5}+36 x^{4}+189 x^{3}](https://tex.z-dn.net/?f=-9%20x%5E%7B5%7D%2B36%20x%5E%7B4%7D%2B189%20x%5E%7B3%7D)
We have to find the factored form of the above given polynomial equation.
Let us solve it by grouping.
Now, take the polynomial ⇒ ![-9 x^{5}+36 x^{4}+189 x^{3}](https://tex.z-dn.net/?f=-9%20x%5E%7B5%7D%2B36%20x%5E%7B4%7D%2B189%20x%5E%7B3%7D)
By taking common term out, we get
![\rightarrow-9 x^{3}\left(x^{2}-4 x-21\right)](https://tex.z-dn.net/?f=%5Crightarrow-9%20x%5E%7B3%7D%5Cleft%28x%5E%7B2%7D-4%20x-21%5Cright%29)
![\rightarrow-9 x^{3}\left(x^{2}-(7-3) x-7 \times 3\right)](https://tex.z-dn.net/?f=%5Crightarrow-9%20x%5E%7B3%7D%5Cleft%28x%5E%7B2%7D-%287-3%29%20x-7%20%5Ctimes%203%5Cright%29)
Grouping the terms we get,
![\rightarrow-9 x^{3}\left(\left(x^{2}-7 x\right)+(3 x-7 x^3)\right)](https://tex.z-dn.net/?f=%5Crightarrow-9%20x%5E%7B3%7D%5Cleft%28%5Cleft%28x%5E%7B2%7D-7%20x%5Cright%29%2B%283%20x-7%20x%5E3%29%5Cright%29)
Taking common terms out from each group,
![\rightarrow-9 x^{3}(x(x-7)+3(x-7))](https://tex.z-dn.net/?f=%5Crightarrow-9%20x%5E%7B3%7D%28x%28x-7%29%2B3%28x-7%29%29)
![\Rightarrow-9 x^{3}((x-7)(x+3))](https://tex.z-dn.net/?f=%5CRightarrow-9%20x%5E%7B3%7D%28%28x-7%29%28x%2B3%29%29)
![\rightarrow-9 x \times x \times x \times(x-7) \times(x+3)](https://tex.z-dn.net/?f=%5Crightarrow-9%20x%20%5Ctimes%20x%20%5Ctimes%20x%20%5Ctimes%28x-7%29%20%5Ctimes%28x%2B3%29)
Thus the factored form of polynomial is found out